A Just & True Love : Feminism at the Frontiers of Theological Ethics : Essays in Honor of Margaret A. Farley - Farley, Margaret A.; Ryan, Maura A., 1957-; Linnane, Brian F. (Notre Dame, Ind. : University of Notre Dame Press, 2007)
"This interdisciplinary and ecumenical collection of essays honors the transformative work of Margaret A. Farley, using it as a starting point for reflection on the contribution of feminist methodology to theology and ethics. Through a variety of perspectives, contributors show that by resisting classical oppositions between "interpersonal" and "social" ethics and by insisting that social, economic, and political realities be taken seriously in considerations of justice, feminist concerns challenge the very categories of Christian ethics."--Jacket.
Freedom-in-relation : autonomy, relationality, solidarity -- Feminist theology and sexual ethics / Lisa Sowle Cahill -- Human rights and women's rights : initiatives and interventions in the name of universality / David Hollenbach -- Transnational feminism and the rhetoric of religion / Serene Jones -- Postcolonial challenges and the practice of hospitality / Letty M. Russell -- A just and true love -- Self and other in a theological framework / Gene Outka -- Justice and love shall kiss / Ada María Isasi-Díaz -- Mouth to mouth, person to person / Ronald R. Garet -- The meaning and practice of love -- Feminist ethics and the sexual abuse of children : reading Christian origins / Mary Rose D'Angelo -- The sexual abuse scandal in the Catholic Church : implications for sexual ethics / Brian F. Linnane -- Framework for love: toward a renewed understanding of Christian vocation / Anne Patrick -- Virtuous decision makers and incompetent patients : the case of the conjoined twins / M. Cathleen Kaveny -- Truth and love in ecclesial community -- Contraceptive use and the authority of the church : a case study on natural law and moral discernment / Jean Porter -- The second great argument about freedom / Leslie Griffin -- John Paul II's understanding of the church as teacher of truth about humankind / Charles Curran -- Neither thick nor thin : politics and polity in the ethics of Margaret A. Farley / William O'Neil.
Includes bibliographical references and index.
"Selected publications of Margaret A. Farley": pages 480-489
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Farley, Margaret A; Feminist ethics; Feminist theology; Christian ethics; Sexual ethics; Medical ethics; Ethics, Medical; Éthique féministe.; Théologie féministe.; Morale sexuelle; Éthique médicale.; Christian ethics; Feminist ethics; Feminist theology; Medical ethics; Sexual ethics; RELIGION / Theology; Feministische Ethik; Feministische Theologie; Feminist ethics; Feminist theology; Christian ethics; Sexual ethics; Medical ethics; Festschriften; Festschriften